The 46, XX Ovotesticular Disorder of Sex Development With Xq27.1q27.2 Duplication Involving the SOX3 Gene: A Rare Case Report and Literature Review - Zhuang, Jianlong; Chen, Chunnuan; Li, Jia; Jiang, Yuying; Wang, Junyu; Wang, Yuanbai; Zeng, Shuhong; Lin, Yiming; Xie, Yingjun (Frontiers in Pediatrics, 2021)
Background: Very few reports are available on human XX ovotesticular disorder of sex development involving SOX3 gene duplication. Here we aim to present a rare case of SOX3 gene duplication in a person from the Chinese population who exhibits XX ovotesticular disorder of sex development. Case Presentation: A 7-year-old Chinese individual from Fujian province in Southeast China was recruited. The patient presented 46, XX karyotype, absence of sex-determining region Y, and was diagnosed with XX ovotesticular disorder of sex development. Furthermore, SNP array analysis demonstrated that the patient had a 2.2-Mb duplication in the Xq27.1q27.2 region (arr[hg19]Xq27.1q27.2:139,499,778-141,777,782) involving the SOX3 gene. Additionally, no SOX3 duplication was observed in the parents or the sibling, who displayed none of the clinical features. Conclusion: We identified the first case of SOX3 duplication in a Chinese individual who exhibits ovotesticular disorder of sex development. Our study strengthens the link between the SOX3 duplication and XX ovotesticular disorder of sex development and indicates that SOX3 is the evolutionary antecedent of sex-determining region Y.